Describing the Buying Behavior of Bank Personnel and their Customer Satisfaction - Lingo-lingo, Shane Kylah T.; Dela Cruz, Leo Mart A.; Codera, Chammilou T.; Sumicad Jr., Eligen H.; Batingal, Ace Virgel T. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The study aims to describe the buying behavior of male and female bank personnel and their customer satisfaction. The buying behavior represents three indicators: perceived benefits, domain of specific innovativeness, and shopping orientation. This study utilizes a descriptive correlational approach, which focuses on describing the significant relationship between the two variables: buying behavior and customer satisfaction. The data of the study is collected using a survey questionnaire distributed to 106 participants in each selected bank. The study’s findings reveal that male and female bank personnel have high impulsivity in terms of perceived benefits, domain of specific innovativeness, and shopping orientation, but male bank personnel have low impulsivity in terms of the domain of specific innovativeness. It also indicates that male and female bank personnel are satisfied with purchasing online; positive product reviews attract them, and the thing that male and female bank personnel are unsatisfied with is the use of credit cards to purchase online. Findings indicate a significant relationship between buying behavior and customer satisfaction of male and female but with a low correlation for male and a moderate correlation for female and indicates no significant difference between the buying behavior of male and female bank personnel. Therefore, male and female bank personnel show an interest in and are highly impulsive in purchasing online.